Development of test operations with different duration in order to improve verification quality of effectiveness formula - Lutsenko, Ihor; Fomovskaya, Olena; Vihrova, Elena; Serdiuk, Olga; Fomovsky, Felix (Eastern-European Journal of Enterprise Technologies, 2018)
Selection of an indicator for assessment of effectiveness of operations is a very essential step, because this choice predetermines the mode of operation for all functional systems at an enterprise. An axiom is the thesis that all technological processes without exception must be optimized using a coordinated optimization criterion. This is possible only in case if the effectiveness formula is used as a unified criterion. Only in this case, maximizing of financial capabilities of an enterprise is provided. In order to identify the original effectiveness formula among a set of estimation indicators, which cannot be distinguished based on formal features, it is necessary to use a scientifically substantiated verification method. A limited class of models of operations with distributed parameters of different duration is determined. Creation of such a class is the most difficult problem, since comparison of operations of different duration requires taking into account the time factor, and the distributed nature of resource consumption and resource transfer in time significantly complicates the problem. To solve this problem, at the first stage, the rules of composition of an operation with distributed parameters using simple global models of operations with different duration were determined. At the second stage, for each simple model of an operation, there was formed a correspondent simple model of an operation with a longer duration, effectiveness of which was higher than that of the original operation by definition. At the final stage, we formed a limited class of global models of operations with distributed parameters of different duration with the use of the original and formed simple models of operations. Development of verification method by determining the class of operations with distributed parameters of different duration significantly enhances reliability and validity of results of verification of the estimation indicator, which is supposed to be used as an effectiveness indicator and an optimization criterion.